2018
DOI: 10.1097/olq.0000000000000809
|View full text |Cite
|
Sign up to set email alerts
|

Multistate Syphilis Outbreak Among American Indians, 2013 to 2015

Abstract: This article summarizes a multi-state outbreak of heterosexual syphilis, including 134 cases of syphilis in adults and adolescents and at least two cases of congenital syphilis, which occurred on an American Indian reservation in the United States during 2013-2015. In addition to providing salient details about the outbreak, the article seeks to document the case-finding and treatment activities undertaken, their relative success or failure, and the lessons learned from a coordinated, multiagency response. Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…All studies showed an under-detection and under-reporting of cases. The studies indicated that the offer of massive rapid testing [ 16 , 23 ], the increase in general and gestational screening for syphilis [ 16 ], health staff training [ 20 , 30 ], intersectoral articulation, and coordinated response with community participation [ 24 , 25 , 29 ] are key points for the control of syphilis in these populations, particularly in remote areas [ 17 ].…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…All studies showed an under-detection and under-reporting of cases. The studies indicated that the offer of massive rapid testing [ 16 , 23 ], the increase in general and gestational screening for syphilis [ 16 ], health staff training [ 20 , 30 ], intersectoral articulation, and coordinated response with community participation [ 24 , 25 , 29 ] are key points for the control of syphilis in these populations, particularly in remote areas [ 17 ].…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…18 We also propose making BPG more affordable by expanding 340B pricing to private practices and using mobile health clinics to delivery BPG to patients' homes. 19 In the interim, although BPG access is still limited, healthcare provider education is needed to know where patients can receive BPG. Finally, consideration should be given to expanding the time interval between therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Six references described an outbreak response for syphilis 4 and gonorrhoea. 2 STI testing and treatment within the Indian Health System are primarily provided in outpatient clinics and emergency departments 37,[73][74][75][76][77][78][79][80][81] and are delivered according to national guidelines. 73 Expedited partner therapy (EPT) is available in some clinical settings.…”
Section: Clinical Service Deliverymentioning
confidence: 99%
“…[76][77][78][79] In some situations, such as outbreaks or in review of local epidemiology, STI screening and clinical decision support can be expanded based on local policy and practice needs. 77,80,81 In comparison to non-Hispanic Whites, AI/AN men and women have been reported to more likely seek STI services. 85,86 Yet, in 2019, nationally recommended routine annual chlamydia screening coverage among women aged 16-25 years in IHS facilities was 35%, with a wide range of delivery across sites (0-54%) (A. Apostolou, pers.…”
Section: Clinical Service Deliverymentioning
confidence: 99%
See 1 more Smart Citation